Peran Kegiatan Ekstrakurikuler Pramuka dalam Membentuk Karakter Disiplin Siswa di Pondok Pesantren Modern Diniyah Pasia - Ramadhan, Muhammad Lutfi; Ikhlas, Al (Lembaga Yasin AlSys, 2024)
At the beginning of the new school year at the Modern Diniyah Pasia Islamic Boarding School, most students do not yet have a good discipline character. Such as violations in the form of students being late to school, not wearing attributes according to the provisions and so on. The efforts made by the school are to require extracurricular scouting activities for students. Because extracurricular scouting activities can shape students' character. The purpose of this study is to determine the process of forming students' disciplined character through scouting activities at the Modern Diniyah Pasia Islamic Boarding School. The method used in this study is a qualitative method with a descriptive approach, the object of this study is the scout members of the Mopdern Diniyah Pasia Islamic Boarding School. The data in this study were obtained from observation, interviews and documentation. In analyzing the data, the author used source triangulation. The results of this study indicate that the process of forming students' disciplined character at the Modern Diniyah Pasia Islamic Boarding School is teachers as role models for students, routine training and sanctions that educate.